Light and temperature effects on sprout yield and its proximate composition and vitamin C content in Lignosus and Mung beans (Journal of the Bangladesh Agricultural University, 2017)
Bean sprout is used as vegetables. The present study investigated the effect of temperature and light on seed germination and sprout yield, and proximate (crude protein, crude fat, crude fibre, nitrogen free extract and ash) composition of sprout in Lignosus (Dipogon lignosus (L.) Verdc.) and Mung (Vigna radiata Wilczek) beans. Three temperatures (ambient, 25o and 30oC) and two light regimes; continuous dark, (CD) and continuous dark alternated by ½ hour light daily, (DAL) were used for seed germination and bean sprout yield. Data were collected 24, 48, 72, 96 and 120 hours after setting the presoaked seeds in the petri dishes. Of the temperature regimes, generally better seed germination and sprout fresh weight (yield) were observed at 25oC in Mung bean and 30oC in Lignosus bean. Germination and sprout yield were similar under CD and DAL. Both under CD and DAL, sprout yield was higher after 120 hours compared to 96 hrs after germination in both the beans. Proximate composition of dry seeds and their sprouts was also determined. Irrespective of species, crude protein content was significantly higher in sprout (average of 29.33%) than dry seed (average of 24.33%).Vitamin C was significantly higher in Lignosus bean sprout (20.93 mg 100g-1) compared to Mung bean sprout (9.52 mg 100g-1). This is the first world report on Lignosus bean sprout. It may be concluded that better sprout yield and good protein content were obtained at 25oC in Mung bean and 30oC in Lignosus bean after 120 hrs of germination irrespective of dark and light.J. Bangladesh Agril. Univ. 15(2): 248-254, December 2017